Analisis Audit Sistem Informasi Menggunakan Framework Committee Of Sponsoring Organizations Of The Treadway Commission (COSO) Pada PT. Persero Batam - Reza Ardiansyah; tata sutabri; Annisa Fitri Aulia (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
An information system (IT) audit is one of the important aspects of maintaining the effectiveness and efficiency of company operations. In this study, an information system audit at PT PERSERO was conducted to determine the extent of the company's capability level and provide recommendations to improve the performance of information systems to achieve the company's business objectives. The control standard used in this study is the Committee of Sponsoring Organizations of the Treadway Commission (COSO) which consists of the components of Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring. The purpose of this study is to evaluate whether the system is equipped with controls that are carried out properly and correctly. From the results of the research, data was obtained through interviews, observations, and document studies, which were analyzed using quantitative descriptive methods. The results showed that the average value of each component ranged from 4.46 to 4.74, with the overall assessment percentage reaching 90.8% and a capability level of 4.54. This shows that the internal control system at PT Persero Batam is in the very good category. The best-performing component is Monitoring Activities (4.74), while Control Environment (4.46) is an area of potential improvement. The gap analysis shows a small difference of 0.16, which indicates that internal control has almost reached the ideal level.